1998
DOI: 10.1007/s002590050238
|View full text |Cite
|
Sign up to set email alerts
|

Application of SPET using technetium-99m sestamibi in brain tumours and comparison with expression of the MDR-1 gene: is it possible to predict the response to chemotherapy in patients with gliomas by means of 99m Tc-sestamibi SPET?

Abstract: Technetium-99m sestamibi (MIBI) is thought to be passively taken up by metabolically active tumour cells and effluxed from them by P-glycoprotein (Pgp). This 170-kDa membrane-bound protein, encoded by the MDR-1 gene, acts as an energy-dependent efflux pump for several antineoplastic agents, resulting in multidrug resistance. For this reason, it is of interest whether the tumour's response to chemotherapy can be predicted by MIBI single-photon emission tomography (SPET). In this study, MIBI SPET was compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…1,8,17,27,37,38) MDR-1 gene expression occurs in gliomas and other tumors. 1,8,38) Study of 99m Tc-MIBI SPECT and MDR-1 gene expression in six gliomas found that four patients with 99m Tc-MIBI SPECT concordance K. Kunishio et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,8,17,27,37,38) MDR-1 gene expression occurs in gliomas and other tumors. 1,8,38) Study of 99m Tc-MIBI SPECT and MDR-1 gene expression in six gliomas found that four patients with 99m Tc-MIBI SPECT concordance K. Kunishio et al…”
Section: Discussionmentioning
confidence: 99%
“…19,38) Previous studies have shown an inverse relationship between the levels of Pgp and the balance of 99m Tc-MIBI uptake and washout rates in tumor cells. 1,4,19,38) However, little is known about such features of 99m Tc-MIBI SPECT in intracranial meningiomas.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among them, [ 99m Tc]sestamibi ( 99m Tc-MIBI) and [ T99mc ] tetrofosmin ( 99m Tc-TF), which are both single-photon emission computed tomography (SPECT) tracers. 99m Tc-MIBI uptake has been proven in vitro and in vivo to be inversely correlated with glioma's MDR phenotype [5][6][7][8][9]. In vitro studies have shown that 99m Tc-TF is influenced to a lesser degree, and thus, 99m Tc-TF may be superior to 99m Tc-MIBI for brain tumor imaging [5,6].…”
Section: Introductionmentioning
confidence: 95%